Melothria scabra [Naudin] Provides New Opportunities for Agronomic Research - Jonathan Daniel Hulse (International Journal of Agricultural Sciences, 2022)
This manuscript attempts to bringMelothria scabra[Naudin] to the attention of agronomic researchers as an increasingly popularand economically important crop and to identify gaps in research that should beinvestigatedwithfuturestudies.Allrelevantpeerreviewedpublications were examined in this study, with 79% of the studies published since 2000 c.e., while the remainder of the studies provide historical context.Major gaps in the research involvingM. scabraoffers a new frontier in agronomic studies, and will increase agronomist’s knowledge of this uniquely meso-American crop species. In conclusion,M. scabrais an understudied crop with world-widecultivation, and offers many opportunities foragronomists to research the genetics, physiology, and morphology of this small melon